2017
DOI: 10.1177/1179299x17710016
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Preoperative Serum Carcinoembryonic Antigen Levels and Expression on Pancreatic and Rectal Cancer Tissue

Abstract: Carcinoembryonic antigen (CEA)–targeted imaging and therapeutic agents are being tested in clinical trials. If CEA overexpression in malignant tissue corresponds with elevated serum CEA, serum CEA could assist in selecting patients who may benefit from CEA-targeted agents. This study aims to assess the relationship between serum CEA and CEA expression in pancreatic (n = 20) and rectal cancer tissues (n = 35) using histopathology. According to local laboratory standards, a serum CEA >3 ng/mL was considered elev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 34 publications
0
13
0
1
Order By: Relevance
“…Because CEA expression on the cell surface of tumors is variable, patient selection before surgery would be beneficial. However, since Boogerd et al described a lack of correlation between tumor CEA expression and serum CEA levels in rectal cancer, serum CEA levels seem inadequate for patient selection. In contrast to rectal cancer, the study did find a significant correlation between serum CEA and the percentage of CEA‐expressing tumor cells in PDAC patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because CEA expression on the cell surface of tumors is variable, patient selection before surgery would be beneficial. However, since Boogerd et al described a lack of correlation between tumor CEA expression and serum CEA levels in rectal cancer, serum CEA levels seem inadequate for patient selection. In contrast to rectal cancer, the study did find a significant correlation between serum CEA and the percentage of CEA‐expressing tumor cells in PDAC patients.…”
Section: Discussionmentioning
confidence: 99%
“…CEA serum measurements are currently used during follow‐up and can indicate local recurrence or metastatic disease when values are rising . Interestingly, a recent histopathological study by Boogerd et al showed lack of correlation between serum CEA and tumor CEA expression in rectal cancer. Most important for fluorescent‐guided surgery, a great difference is seen in expression levels of CEA between CRC tissue and healthy tissue (60‐fold) .…”
Section: Cea and Crcmentioning
confidence: 99%
“…La présence d'ACE circulant qui est parfois citée comme problème potentiel n'en est pas un, car les patients concernés par la FGS ont, en général, un taux d'ACE circulant qui ne va pas perturber la captation tumorale d'un anticorps anti-ACE injecté par voie intra-veineuse à des doses de quelques milligrammes. En outre, Boogerd et al ont montré que le niveau d'ACE circulant ne reflète pas toujours le niveau d'expression de l'ACE par la tumeur, notamment chez les patients présentant une tumeur colorectale [36]. Dans cette étude, 32 patients atteints de cancer rectal sur 35 patients avaient une forte expression d'ACE au niveau tumoral.…”
Section: Revuesunclassified
“…Uncharacteristically for a single chain fragment, pharmacokinetics were rather slow, and liver uptake was high relative to other organs. In another study by the same authors, a correlation was found between serum CEA levels and PDAC tumour expression of CEA, allowing selection of PDAC patients who might benefit from CEA-targeted imaging [ 79 ].
Fig.
…”
Section: Cathepsinsmentioning
confidence: 99%